The Effect of Means-Tested Transfers on Work: Evidence from Quasi-Randomly Assigned SNAP Caseworkers - Jason B. Cook; Chloe N. East (CESifo GmbH, 2024)
Supplemental Nutrition Assistance Program (SNAP) is the backbone of the U.S. safety net. We provide the most comprehensive and generalizable evaluation of the labor supply effects of access to modern SNAP to date. To do so we use new, rich administrative data and an examiner design based on conditional random assignment of SNAP applicants to caseworkers. We find no evidence of large or lasting negative effects of SNAP on labor supply. We also provide the first large, quantitative evaluation of the role of SNAP caseworkers in determining applicants' outcomes.
Keywords: H53; I38; J22; 330; SNAP; labor supply; caseworker